Pemberdayaan Literasi Digital Masyarakat Desa melalui Pelatihan Pembuatan Koran Digital di Desa Olean - Nonny Rulisty Putri Sutikno; Raudatul Jannah; Ria Murdani; Yasmin Naini Bahanan; Ahmad Ihsan (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
The development of information technology encourages rural communities to improve their digital literacy skills to support the dissemination of information and the promotion of local potential. However, limited skills in managing digital media have caused village information to be inadequately documented and published. This community service program aimed to enhance community digital literacy through digital newspaper creation training in Olean Village. The implementation method employed a participatory approach consisting of socialization, village news writing training, digital newspaper design practice using Canva, and assistance in digital media publication. The participants included community members and village officials who were actively involved throughout the training activities. The results showed that participants were able to write simple news articles, manage village activity documentation, and independently design digital newspapers. In addition to improving participants’ digital skills, the program also produced a village-based digital information medium that can be utilized to promote village activities and local potential. Therefore, this program contributes to strengthening community digital literacy and developing village information media that are more adaptive to technological advancements.